2010
DOI: 10.1111/j.1574-6968.2010.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptaibols induce defense responses and systemic resistance in tobacco against tobacco mosaic virus

Abstract: Trichoderma spp. are well-known biocontrol agents because of their antimicrobial activity against bacterial and fungal phytopathogens. However, the biochemical mechanism of their antiviral activity remains largely unknown. In this study, we found that Trichokonins, antimicrobial peptaibols isolated from Trichoderma pseudokoningii SMF2, could induce defense responses and systemic resistance in tobacco (Nicotiana tabacum var. Samsun NN) against tobacco mosaic virus (TMV) infection. Local Trichokonin (100 nM) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 32 publications
4
63
0
1
Order By: Relevance
“…As was shown previously, some peptide antibiotics synthesized by Trichoderma sp. can significantly reduce the development of TMV in tobacco plants (Nicotiana tabacum) [24]. It was suggested that an increased level of reactive oxygen species, like we observed in our study, might indicate that substances synthesized by fungi induce immunity in the infected plants.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As was shown previously, some peptide antibiotics synthesized by Trichoderma sp. can significantly reduce the development of TMV in tobacco plants (Nicotiana tabacum) [24]. It was suggested that an increased level of reactive oxygen species, like we observed in our study, might indicate that substances synthesized by fungi induce immunity in the infected plants.…”
Section: Discussionsupporting
confidence: 70%
“…by antibiosis [4]. Some antibiotics synthesized by microorganisms may be active against viruses [6,24]. As was shown previously, some peptide antibiotics synthesized by Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
“…Each compound exhibits a specific antibiotic activity and each Trichoderma strain hasd different antagonistic effect on different pathogens. Secondary metabolites serve a pivotal function in antagonistic activities against Fusarium and also act as sporogenic factors and growth promoters that affect morphological differentiation in mycoparasitic Trichoderma [30,31]. In view of this specific secondary metabolites could be of a commercially viable alternative for controlling phytopathogens rather than whole organism formulations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many MAMPs have been identified for PGPR, such as flagellin or lipopolysaccharides, but also secreted compounds including antibiotics, biosurfactants and volatile organic compounds have been shown to elicit systemic resistance. Effective Trichoderma strains produce a variety of MAMPs (Table 1), which to date are those most widely described among T. pseudokoningii Induces the production of ROS, the accumulation of phenolic compounds at the application site and virus resistance in tobacco plants through multiple defence signalling pathways Luo et al (2010) 18mer peptaibols T. virens Elicitation of cucumber systemic defences against P. syringae The Trichoderma-plant interaction plant-beneficial fungi (Lorito et al, 2010). The first recognized Trichoderma MAMP was identified as an ETinducing xylanase (Xyn2/Eix), produced by Trichoderma as a potent elicitor of plant defence responses in specific tobacco and tomato cultivars (Rotblat et al, 2002).…”
Section: Induction Of Plant Defences By Trichodermamentioning
confidence: 99%
“…lachrymans (Viterbo et al, 2007). The protection of tobacco plants against tobacco mosaic virus by Trichoderma peptaibols was shown to involve multiple defence signalling pathways (Luo et al, 2010).…”
Section: Induction Of Plant Defences By Trichodermamentioning
confidence: 99%